Intra‐familial variability associated with recessive RYR1 mutation diagnosed prenatally by exome sequencing. (2nd October 2016) - Casey, Jillian; Flood, Karen; Ennis, Sean; Doyle, Emma; Farrell, Michael; Lynch, Sally Ann
Abstract: Objective: To determine the underlying molecular aetiology in a non‐consanguineous Irish family who have had three fetal losses because of a primary myopathy characterised by fetal akinesia, arthrogryposis multiplex, bilateral pulmonary hypoplasia and reduced muscle bulk. Methods: Fetal DNA extracted from amniotic cells was whole genome amplified and subjected to whole exome sequencing. Results: Whole exome sequencing identified compound heterozygous variants in RYR1 as the cause of the lethal myopathy in this family. All three fetuses were compound heterozygous for a paternally inherited missense variant (c.2113G > A; p.Gly705Arg) and a novel maternally inherited truncating frameshift deletion (c.8843delC; p.Ser2948Cysfs*58). This family did not have the classic cores and fibre type disproportion typically associated with RYR1 mutation. The RYR1 exome finding was made during the couple's third pregnancy and enabled prenatal genetic testing to be undertaken. Conclusion: We show that recessive RYR1 mutations can be associated with significant intra‐familial variability in clinical presentation which can complicate prediction of clinical outcome. RYR1 mutations can also cause diverse muscle pathologies which thwarts diagnosis. This study demonstrates the impact that exome‐based diagnoses can have for families with lethal disorders. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Dominant and recessive mutations in the RYR1 gene can cause central core disease of variable severity, ranging from a severe neonatal form with prenatal onset to a classic congenital myopathy Recently RYR1 has been associated with fetal akinesia syndrome with prenatal lethality or early postnatal death, with less than 20 reported cases Cores and fibre type disproportion are the classic features of RYR1‐associated pathology What does this study add? RYR1 is associated with intra‐familial variability which can make it difficult to predict clinical severity and outcome Recessive RYR1 mutations can cause extremely diverse muscle pathologies which can thwart diagnosis Whole exome sequencing can be successfully performed on whole genome amplified fetal DNA extracted from amniotic cells, which raises the possibility of undertaking NGS diagnosis in cases where the concentration or total amount of extracted fetal DNA is suboptimal